2008
DOI: 10.1007/s11999-008-0418-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported Outcome Correlates With Knee Function After a Single-design Mobile-bearing TKA

Abstract: With substantial interest devoted to improving knee flexion after TKA, it is important to document the relationship between high range of motion and patient-rated outcomes shown. We therefore asked whether single-design high-flexion mobile-bearing posterior-stabilized TKA resulted in: (1) improved knee function; (2) satisfying subjective results; (3) participation recreational and sporting activities; and (4) function correlated to the final range of motion. We prospectively followed 445 consecutive patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 26 publications
1
34
1
Order By: Relevance
“…Range of motion did not correlate with patient-reported function in high-flexion activities. This contrasts with the results of Argenson et al [29], who found that knee flexion greater than 125°after high-flexion TKR was associated with improved patient-reported outcomes as measured by KOOS subscores. These authors did not specifically evaluate function in deep knee flexion, and we did not utilize the KOOS instrument.…”
Section: Discussioncontrasting
confidence: 95%
“…Range of motion did not correlate with patient-reported function in high-flexion activities. This contrasts with the results of Argenson et al [29], who found that knee flexion greater than 125°after high-flexion TKR was associated with improved patient-reported outcomes as measured by KOOS subscores. These authors did not specifically evaluate function in deep knee flexion, and we did not utilize the KOOS instrument.…”
Section: Discussioncontrasting
confidence: 95%
“…In one study, however, analyzing the results of 67 patients undergoing TKA for an association of obesity with pain outcomes [17], BMI of 35 to 40 kg/m 2 was associated with higher pain scores in multivariable-adjusted models that included age, gender, and comorbidities. In our earlier experience [2], pain at the proximal aspect of the tibia was observed for obese women. It was our hypothesis that a stem would limit the effect of the load during gait and consecutively limit the pain.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies concluded that consideration should be given to additional tibial fixation in patients with obesity [1]. Based on our clinical experience [2] and the results of recent studies [1,6,23] we hypothesized that a stemmed tibial component would improve function, patient-reported outcomes, and reduce complications after TKA in patients with obesity. Therefore, it was our aim to compare (1) function and pain (as measured by the new KSS, KOOS, and VAS pain scores); (2) quality of life (as measured by SF-12); and (3) mechanical complications and premature revision (defined as revision before 2 years) between patients with obesity undergoing TKA (BMI [ 30 kg/m 2 ) who received either a stemmed or an unstemmed tibial Although some differences in pain and function were found in favor of stemmed tibial components, in many other important areas, we found no such differences; and, importantly, the observed differences were small in magnitude and so were unlikely to have been clinically important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total knee arthroplasty (TKA) procedures require high functionality and durability and deep knee flexion is considered to be especially important as an indicator of higher function [1]. Many high-flex type prostheses have been developed to enable deep knee flexion.…”
Section: Introductionmentioning
confidence: 99%